JOINT COST ANALYSIS AS AN AID TO MANAGEMENT. - Lorig, Arthur N. (The Accounting Review, 1955)
Abstract Since joint product costing is itself a costly process, it seems important to be assured that the results are worth the cost. The uses, which can be made of joint cost calculations, are not usually clearly defined. The main use, and the only one commonly recognized, is the pricing of joint products in inventories. For management guidance, the separation of joint costs by the joint products is assumed to serve no useful purpose. The products originate from common materials and a common processing up to the split-off point and are inseparable up to that point. Managerial decision cannot be exercised as to whether or not to exclude one or more of the products in the processing; they must all be produced or none. Furthermore, the chance to vary their relative quantities in the short run is practically non-existent. Hence management gains as much control information from their total combined cost figures up to the split-off point as it would from those same joint costs divided among the products.